(untitled) (Asian Journal of Medical and Biological Research, 2021)
Medical record is the most important document in the medical field. This cross sectional study was conducted at Chittagong Medical College hospital from January to December, 2017 with the aim to assess the existing medical record keeping practices. Around 214 patients’ record files were selected by systematic sampling method and 30 record keeping personnel were also interviewed. Data were collected by review of records by observational checklist and semi-structured questionnaire were administered to medical record keeping personnel. This study showed that, out of 44 items of patient record file among them 33 items were recorded in 100%. Majority of the medical records (89.7%) were satisfactorily completed. All of the respondents mentioned that they had no training regarding medical record keeping practices. All the respondents stated that some problem faced during keeping the medical record and (90.0%) respondents stated that computerized medical record system could solve the problem they faced. This study showed that, the medical recording status is good in majority areas but keeping practice was not organized at all. There were important defects in keeping the medical records. It seems that there are multiple factors contributing to the problem, such as lack of manpower, insufficient record room and they had no training about medical record keeping practice. It is necessary for the government to develop policies and strategies to improve medical record keeping practice for patient safety, to reduce error, repetition of investigations, protect the medico legal issues and future health care advancement. Asian J. Med. Biol. Res. December 2020, 6(4): 723-730